2019
DOI: 10.3390/s19245529
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion Detection of UAVs Based on the Deep Belief Network Optimized by PSO

Abstract: With the rapid development of information technology, the problem of the network security of unmanned aerial vehicles (UAVs) has become increasingly prominent. In order to solve the intrusion detection problem of massive, high-dimensional, and nonlinear data, this paper proposes an intrusion detection method based on the deep belief network (DBN) optimized by particle swarm optimization (PSO). First, a classification model based on the DBN is constructed, and the PSO algorithm is then used to optimize the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…T . For each particle in the population, fitness value can be obtained according to fitness function to evaluate the fitness of particles [22]. This paper adopts the fitness function proposed by Vieira [23], as shown in (1), where α is a hyperparameter, which can coordinate the relationship between the classifier performance P (including accuracy, F-score, precision, etc.)…”
Section: Background a Partical Swarm Optimization (Pso)mentioning
confidence: 99%
“…T . For each particle in the population, fitness value can be obtained according to fitness function to evaluate the fitness of particles [22]. This paper adopts the fitness function proposed by Vieira [23], as shown in (1), where α is a hyperparameter, which can coordinate the relationship between the classifier performance P (including accuracy, F-score, precision, etc.)…”
Section: Background a Partical Swarm Optimization (Pso)mentioning
confidence: 99%
“…PSO and its variants are widely used in network intrusion detection. Tan et al [25] proposed to use PSO algorithm to optimize deep belief network (DBN) and apply it to network intrusion detection. Their results showed that the effect of PSO was superior to intelligent optimization algorithms such as genetic algorithm (GA) and simulated annealing (SA), thus the PSO-DBN model also performed other machine learning models.…”
Section: Related Workmentioning
confidence: 99%
“…However, in [25], [26], the results only gave the overall metrics of the algorithm on the dataset, including accuracy, fmeasures and so on, but not the performance of the algorithm in each class. In network intrusion detection, common types of attacks are easier to detect, such as Dos attacks; while rare types of attacks, such as R2L and U2R, are more difficult to detect, because the system does not have enough database about the features of these attacks.…”
Section: Related Workmentioning
confidence: 99%
“…The machine learning (ML) algorithms mentioned above depend on complex feature engineering and are difficult to adapt to the growing network environment, while the deep learning (DL) algorithm can autonomously abstract high-level features from basic network traffic without complex feature engineering; therefore, it is widely used in attack recognition tasks. Tan et al [18] obtained a structure-optimal deep belief network (DBN) optimized by the particle swarm optimization (PSO) method, and experiments showed that the accuracy of PSO-DBN on the KDD99 dataset reached 92.44%. Marir et al [19] applied DBN as a feature selector and combined it with an SVM classifier to improve the recognition accuracy of IDS.…”
Section: Introductionmentioning
confidence: 99%